If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 + -4x = 2x + 24 Reorder the terms: 90 + -4x = 24 + 2x Solving 90 + -4x = 24 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 90 + -4x + -2x = 24 + 2x + -2x Combine like terms: -4x + -2x = -6x 90 + -6x = 24 + 2x + -2x Combine like terms: 2x + -2x = 0 90 + -6x = 24 + 0 90 + -6x = 24 Add '-90' to each side of the equation. 90 + -90 + -6x = 24 + -90 Combine like terms: 90 + -90 = 0 0 + -6x = 24 + -90 -6x = 24 + -90 Combine like terms: 24 + -90 = -66 -6x = -66 Divide each side by '-6'. x = 11 Simplifying x = 11
| (x+3)=3 | | 2X+33=4X+31 | | 3x^2-2x-33=0 | | [x+3]=3 | | 16-9t^2=0 | | 3x-3=2x | | 6.4x-4.9x=-45 | | 5c^3=20c | | 9-5n+1=15 | | 4c+3-2c+7= | | 5x+6=4x+2 | | F=24l | | 4x+25=12x-55 | | (0)+3y=12 | | V^2+7v-18= | | 12x-29=7x+1 | | 8(3n+5)=-32 | | b+b+b+b= | | x+(x+1)+(x+2)=222 | | 3a+3b= | | 3b+3b= | | 9x-4y=-11 | | 3a+8a= | | 9n-28=53 | | -2(-5)(-10)= | | 2(x+5)=3(x-10) | | 22-5x=-28 | | 3x^2+2x-30=0 | | (-5)(10)= | | y+-4=-15 | | 3X^2+10X=-2 | | 9= |